Extracts of Andrographis paniculata (Burm.f.) Nees Leaves Exert Anti-Gout Effects by Lowering Uric Acid Levels and Reducing Monosodium Urate Crystal-Induced Inflammation - Rahmi, Eldiza Puji; Kumolosasi, Endang; Jalil, Juriyati; Buang, Fhataheya; Jamal, Jamia Azdina (Frontiers in Pharmacology, 2022)
Andrographis paniculata has been found to have anti-inflammatory and immunostimulatory effects. This study was to investigate antihyperuricemic and anti-inflammatory effects of A. paniculata leaf extracts. Andrographolide, 14-deoxy-11,12-didehydroandrographolide, and neoandrographolide were quantified in 80% ethanol (EtOH80) and water extracts using HPLC analysis. Antihyperuricemic activity was evaluated using a spectrophotometric in vitro inhibitory xanthine oxidase (XO) assay. The most active extract and andrographolide were further investigated in a hyperuricemic rat model induced by potassium oxonate to determine serum and urine uric acid levels, liver XO activity, followed by Western blot analysis for URAT1, GLUT9 and OAT1. Anti-inflammatory activity was assessed by in vitro inhibitory assay for IL-1α, IL-1β, IL-6, IL-8, and TNF-α in MSU crystal-induced HFLS cells, followed by Western blot analysis for the expression of MyD88, NLRP3, NF-κB p65, and caspase-1 proteins. In vivo assay of the most active extract and andrographolide were performed based on the swelling rate and inhibition of pro-inflammatory mediator release from synovial fluid of a rat knee joint induced by MSU crystals. The results showed that the EtOH80 extract had a greater amount of andrographolide (11.344%w/w) than the water extract (1.379%w/w). In the XO inhibitory activity, none of the samples exhibited greater than 50% inhibition. However, in a rat model, EtOH80 extract (200 mg/kg/day) and andrographolide (30 mg/kg/day) decreased serum uric acid levels and reduced liver XO activity, reduced the protein expression levels of URAT1 and GLUT9, and restored the decrease in OAT1 levels. In the in vitro anti-inflammatory study, EtOH80 extract and andrographolide significantly decreased production of IL-1α, IL-1β, IL-6, and TNF-α, as well as inhibited the synthesis of MyD88, NLRP3, NF-κB p65, and caspase-1 in a concentration-dependent manner, almost comparable to dexamethasone. The EtOH80 extract (200 mg/kg/day) and andrographolide (30 mg/kg) significantly decreased swelling rate and IL-1α, IL-1β, IL-6, and TNF-α in the synovial fluid of rat models in a time-dependent manner, comparable to indomethacin (3 mg/kg/day). In conclusion, the findings show that EtOH80 extract has a substantial anti-gout effect by lowering uric acid levels and suppressing pro-inflammatory mediator production due to the andrographolide content, that might be beneficial in the treatment of gouty-inflammation.